2016
DOI: 10.1208/s12249-016-0501-7
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Assessment of Docetaxel Formulation Developed for Esophageal Stents

Abstract: Abstract. Esophageal cancer (EC) mostly affects the elderly population and is frequently diagnosed at an advanced stage. Self-expanding metal stents (SEMS) are the most popular mode of palliation, but they are associated with reocclusion caused by tumor growth. To overcome this problem, docetaxel (DTX)-loaded polyurethane formulations were prepared for stent application. The films were evaluated against the cancer cell lines, OE-19 and OE-21, and normal esophageal cell line Het-1A. The DTX and the formulations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The reviewed articles were selected from among those extracted through a systematic review of the guidelines [5][6][7] to avoid bias from the article selection process. However, 14 articles [29][30][31][32][33][34][35][36][37][38][39][40][41][42] were added for the further exploration of topics that were not included in the guidelines. In the guidelines, the Japan Medical Library Association was entrusted with a systematic search of the literature published from January 2000 to August 2020.…”
Section: Selection Of Articlesmentioning
confidence: 99%
See 1 more Smart Citation
“…The reviewed articles were selected from among those extracted through a systematic review of the guidelines [5][6][7] to avoid bias from the article selection process. However, 14 articles [29][30][31][32][33][34][35][36][37][38][39][40][41][42] were added for the further exploration of topics that were not included in the guidelines. In the guidelines, the Japan Medical Library Association was entrusted with a systematic search of the literature published from January 2000 to August 2020.…”
Section: Selection Of Articlesmentioning
confidence: 99%
“…Controlled drug elution is often achieved using a drug-impregnated polymer membrane or coating that acts as a drug reservoir for sustained drug release [39]. Several approaches and drug-polymer combinations have been employed to create drug-eluting stents that deliver chemotherapy drugs, including 5-fluorouracil, paclitaxel, and docetaxel, for the treatment of esophageal cancer [40,41].…”
Section: Stent Type and Efficacymentioning
confidence: 99%
“…Although there are few orthotopic esophageal cancer models, in the past decades there are many reports about the use of animals for the test of esophageal stents in vivo . Shaikh et al used a nude mice xenograft tumor model to test docetaxel (DTX)-loaded polyurethane formulations for stent application [84]. To test the esophageal tissue responses to nitinol stents loaded with 50% 5-FU or PTX, Guo et al used twenty-three healthy Bama minipigs to test 4 groups for stent implantation: PTX stent, 5-FU stent, blank film–covered stent, and bare stent.…”
Section: Animal Models For Esophageal Stentsmentioning
confidence: 99%
“…Oesophageal cancer is often diagnosed at an advanced stage and is the sixth most common cause of cancer‐related mortality; moreover, information on the use of DES for this cancer type is meagre. A recent study investigated the use of self‐expanding metallic docetaxel stents to maintain oral alimentation and identified encouraging formulations . Wang et al developed a new approach for making nitinol stents loaded with a high dose of 5‐fluorouracil or paclitaxel with the aim of achieiving unidirectional, sustained and prolonged drug release towards the area of exposure, thus avoiding washout of the drug by oesophageal fluids and systematic administration.…”
Section: Des Targeted For Cancer Therapymentioning
confidence: 99%
“…A recent study investigated the use of self-expanding metallic docetaxel stents to maintain oral alimentation and identified encouraging formulations. 75 Wang et al 76 developed a new approach for making nitinol stents loaded with a high dose of 5-fluorouracil or paclitaxel with the aim of achieiving unidirectional, sustained and prolonged drug release towards the area of exposure, thus avoiding washout of the drug by oesophageal fluids and systematic administration. It was shown that the stent did not cause severe damage to the oesophagus walls and effectively inhibited inflammation, ulceration and granulation tissue growth, which is suggestive of hopeful treatment modality.…”
Section: Micro-rna (Mirna) Facilitated Ges Deliverymentioning
confidence: 99%